Mathematical Characterization of Inorganic Salt Precipitation From the Reaction of CO2 With Formation Brine and Its Application - Yuan, Zhou; Liao, Xinwei; Zhang, Kuaile; Zhao, Xiaoliang; Chu, Hongyang; Zou, Jiandong (Frontiers in Energy Research, 2020)
In the process of CO2 enhanced oil recovery (CO2-EOR), CO2 interacts with formation brine containing high concentrations of scale-forming ions to produce inorganic salt precipitation, which blocks the rock pore throats, changes the characteristics of the reservoir, and thereby reduces the oil recovery rate. In this study, a series of experiments on the static reaction of CO2–formation brine was conducted. The amounts of precipitation formed from the interaction of CO2–formation brine under various conditions were tested. Using the PHREEQC software, the mathematical characterization formulas between the precipitation amount and various environmental factors (e.g., temperature, pressure difference, scale-forming ion concentration, and pH) were established. On this basis, a numerical simulation model of CO2 flooding in a typical area of oil field C was established. The distribution of inorganic salt precipitation during continuous gas flooding was predicted, and the effect of inorganic salt precipitation on oil field recovery was analyzed.